Height and Weight fail to detect early signs of malnutrition in children with cystic fibrosis - Stapleton, Denise; Kerr, Deborah; Sherriff, Jillian; Gurrin, L.; Sly, P. (Lippincott Williams and Wilkins, 2001)
BACKGROUND: Many children with cystic fibrosis grow poorly and are malnourished. This study was undertaken to determine whether extensive anthropometry could detect early signs of malnutrition in prepubertal children with cystic fibrosis to prevent deficits in height and weight. METHODS: Height, weight, six skin folds (triceps, subscapular, supraspinale, abdominal, front thigh, and medial calf) and five girths (arm relaxed, forearm, chest, thigh, and calf) were measured in a cross-sectional study of children aged 6 to 11 years with cystic fibrosis. RESULTS: The children with cystic fibrosis were shorter and lighter for their age and gender than those in the reference groups. The mean weight and height z scores for the girls with cystic fibrosis were lower than those for the boys, significantly so for z weight ( P < 0.05). Although, the mean percent ideal body weight value of 98.6% suggested that the children with cystic fibrosis were adequately nourished, most of the measures of muscularity and adiposity of the children with cystic fibrosis were significantly lower than those of the reference group ( P < 0.05). The z scores of the anthropometric measures revealed that the deficit in muscularity of the children with cystic fibrosis was relatively much greater than the deficit in adiposity. CONCLUSIONS: The percent ideal body weight index does not seem to be an adequate measure of nutritional status in children with cystic fibrosis. Anthropometric assessments should include skin-fold and circumference measurements of numerous sites on the upper and lower body, the trunk, and the limbs to detect deterioration in nutritional status early. Early detection of deficits in nutritional status may result in the adverse effects of malnutrition on height and weight, and possibly clinical status, being prevented.